Pengaruh Pemberian Biofungisida (Gliocladuim sp.) untuk Mengendalikan Penyakit Layu Fusarium (Fusarium sp.) pada Tanaman Cabai Merah Keriting (Capsicum annum L.) - Yupendi, Asri; Putri, Santi Diana; Sari, Wilna; Taufiqqurahman, Taufiqqurahman (UNIVERSITAS LABUHANBATU, 2024)
Curly red chili production has decreased due to disease attacks, one of which is fusarium wilt disease caused by Fusarium sp. fungus. This disease can cause significant losses, even crop failure. Control using chemical fungicides often has a negative impact on the environment and consumer health, so safer alternatives are needed. This study aims to evaluate the effectiveness of Gliocladium sp. dosage as a biological control agent against Fusarium wilt disease in curly red chili plants. This study used a completely randomized design (CRD), with treatments A (control), B (30 grams of Gliocladium sp./polybag), C (60 grams of Gliocladium sp./polybag), D (90 grams of Gliocladium sp./polybag), E (120 grams of Gliocladium sp./polybag), F (180 grams of Gliocladium sp./polybag). The parameters observed were growth percentage (%), attack intensity (%), plant height (cm), number of fruits per plant (fruit), and fruit weight per plant (gram). The results of the effect of Gliocladium sp. to control fusarium wilt disease in curly red chili plants (Capsicum annum L.) concluded that the application of Gliocladium sp. has a significant effect on the growth and yield of curly red chili plants (Capsicum annum L.). Doses of 60, 120 and 180 grams per polybag proved effective in increasing the percentage of plant growth to 100% and suppressing the intensity of disease attack to 0%, showing the potential of Gliocladium sp. as an effective biological control agent. Although the effect on plant height was not statistically significant, there was an increasing trend with the best result at 120 grams per polybag (39.3 cm). Plant productivity also increased, indicated by an increase in the number of fruits per plant (optimal at a dose of 180 grams per polybag with 16 fruits) and fruit weight per plant (highest at a dose of 60 grams per polybag with 45 grams). Keywords: gliocladium sp., fusarium wilt disease, curly red chili